2013
DOI: 10.1021/cg401324f
|View full text |Cite
|
Sign up to set email alerts
|

Achiral Metastable Crystals of Sodium Chlorate Forming Prior to Chiral Crystals in Solution Growth

Abstract: Chiral symmetry breaking in NaClO3 crystallization from an aqueous solution with perturbations has been of great interest. To understand the mechanism, several models focusing on the early stage of the crystallization have been proposed. However, they are ambiguous because the early stage has been barely explored directly. Here, we investigate the early stages of the crystallization process driven by droplet evaporation using a combination of direct in situ microscopic observations and cryogenic single-crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 27 publications
4
50
0
Order By: Relevance
“…Conversely, the opposite handedness is inhibited by a decrease in solution concentration. 255 However, Viedma 256 reports that agitation crystallization results in massive "transient" primary nucleation and complete symmetry destruction. In other words, the chiral purity and the complete symmetry destruction in the crystallization process can be achieved without the initial single chiral intervention.…”
Section: Can Secondary Nucleation Alway Promote Chiral Resolution?mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the opposite handedness is inhibited by a decrease in solution concentration. 255 However, Viedma 256 reports that agitation crystallization results in massive "transient" primary nucleation and complete symmetry destruction. In other words, the chiral purity and the complete symmetry destruction in the crystallization process can be achieved without the initial single chiral intervention.…”
Section: Can Secondary Nucleation Alway Promote Chiral Resolution?mentioning
confidence: 99%
“…If the nucleation rate of these subcrystals is faster than the random primary nucleation rate of new crystals, it may induce the formation of a single chiral solid. Other claims are that because the secondary nuclei has the same handedness as the Eve crystal, Eve’s handedness is amplified. Conversely, the opposite handedness is inhibited by a decrease in solution concentration .…”
Section: Effect Of Secondary Nucleation On Crystallization Outcomementioning
confidence: 99%
“…Our proposed mechanism is based on observations of crystallization made previously in our group for molten NaClO 3 , and by Niinomi et al for aqueous solutions. 20,36 The solid transformation of NaClO 3 from the monoclinic phase III to cubic phase I involves a coordinated sliding of crystal layers. It may also involve another intermediate phase (phase II) which contains equal numbers of left-handed and right-handed sodium-ion octahedra.…”
Section: Discussionmentioning
confidence: 99%
“…Optical microscopy experiments by Niinomi et al on evaporating microdroplets of sodium chlorate solution, revealed that the achiral phase III of sodium chlorate forms first, and later transforms to phase I, apparently following Ostwald's rule of stages 36,38. Niinomi et al showed that nucleation can be promoted by using absorption of CW laser light at high powers, or by excitation of plasmon resonances in Ag nanoparticles or nanolattices.39- 42 Reviewing all the evidence currently available for this system leads us to conclude that primary nucleation of NaClO 3 directly to the chiral phase I is at least hindered, or indeed might not occur at all, i.e., that spontaneous ambient crystallizations of NaClO 3 involve phase III.If we accept that nucleation of phase I is hindered, nucleation of phase III can explain the selectivity in the present work.…”
mentioning
confidence: 99%
“…We recently discovered that a giant crystal enantiomeric excess (CEE) could be observed in the nucleation rate during the chiral crystallization of NaClO 3 induced by excitation of the localized surface plasmon resonance of metal nanoparticles irradiated by circularly polarized laser light in solution. Chiral crystallization is the formation of chiral crystals from an achiral compound and is analogous to absolute asymmetric synthesis in that the product undergoes an achiral–chiral transition. We have demonstrated that a CEE of about 25% can be induced in chiral crystallization of NaClO 3 initiated by heterogeneous nucleation on silver (Ag) nanoaggregates optically trapped by a CPL visible laser (λ = 532 nm) at an air–solution interface . Cheng et al later reported that CEE values exceeding 50% could be attained when, instead of Ag nanoaggregates, a well-defined gold (Au) triangular trimer nanostructure with 3-fold rotational symmetry and a nanogap at its center was excited by a near-infrared CPL laser (λ = 1064 nm) .…”
Section: Introductionmentioning
confidence: 99%